The Legal Values of the Formal Composition in the Interior Spaces of Beauty Centers as a Model - Liqa Ahmad Abd al- Rhman; Rana Abdalkareem Saieed (Journal of Techniques)
The interior spaces of beauty centers. The researcher found that the formal composition of the interior design vocabulary in beauty centers can achieve notional values   through the features that these vocabulary excel in, some of which are related to direct relations with the interior space that contains functional and performance harmony, including those related to In the light of the foregoing, the research problem can be formulated by the following question: What are the legal values   in the formal formation of the interior spaces of beauty centers? On the legal values   in the formal formation of the interior spaces of beauty centers, the methodology adopted by the researcher has been clarified, which is the descriptive approach. In the analysis of the sample, the fourth chapter included the findings of the researcher that the legal values   in the interior design in the reception space of the beauty centers achieved the aesthetic taste as a legal value that is consistent with the perception, where the perception begins aesthetically and then moves to the details, and self-realization as a legal value is a need from The individual’s needs mean using all his capabilities, abilities and talents to be more creative. The interior designer of the beauty centers’ space was able to realize himself in the reception space of the centers that the system is a formal structure subject to formal limitations in order to gain acceptance. The designer relied on creating a system in the design of the reception space for the centers Beautification is a creative act that controls the parts to give their meanings and connotations, that privacy is the individual's need to practice his privacy without monitoring and follow-up from others and in the interior design the recipient's feeling of safety, participation and respect through what the design product carries and this is what the interior designer tried to achieve in the design of the reception space of beauty centers.